The design and development of motion detection edutainment maths for use with slow learners’ children - Parhizkar, Behrang (2022)
This research is aimed to examine game-based motion detection technology in helping slow learners’ children to improve and enhance their levels of attention and concentration while learning mathematics. The study also aims to explore that game-based motion detection engage slow learners’ children while learning mathematics. Additionally, the current study examined the role of game-based motion detection in improving the attention and concentration of slow learners’ children as compared to normal healthy students, in terms of learning mathematics and the educational outcomes of such classes